Error en transmisión de datos de señal electrocardiográfica comprimida empleando cuantificación vectoral - Aparicio Pico, Lilia Edith; Arco Ríos, Pedro José (Ingeniería, 1999)
In the compression electrocardiographic signal transmission using vectorial quantification (VQ), is important to protect the information due to the influence than occasional mistakes produced for the high compression rates in the transmission; needing here an error analisys during transmission and the error stimation study, all these to obtain an error control machine that solve the cases that can appear in a random way during the reduced data transmission of the signal.